2006
DOI: 10.1016/s1479-3563(06)07014-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Access to Credit on Household Welfare in Rural Vietnam

Abstract: In this paper, we investigate the determinants of household borrowing from the formal financial sector, the determinants of credit rationing by the formal sector and the impact of credit on household welfare in rural Vietnam. We find that education, savings, the area devoted to farming and the availability of formal credit are important determinants of both household borrowing and credit rationing by the formal sector. We also find that credit has a positive (albeit small) effect on household welfare in rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 18 publications
2
23
0
4
Order By: Relevance
“…Micro-credit and transfers are very important for household to increase income and consumption. In Vietnam, several studies find positive effects of micro-credit and transfers on household welfare (e.g., Quach and Mullineux, 2007;Nguyen, 2008;Van den Berg and Nguyen, 2011;Nguyen, 2013). Credit and transfers can help households who are affected by natural disasters smooth their consumption (Sawada, 2006).…”
Section: Resilience To Disastersmentioning
confidence: 99%
“…Micro-credit and transfers are very important for household to increase income and consumption. In Vietnam, several studies find positive effects of micro-credit and transfers on household welfare (e.g., Quach and Mullineux, 2007;Nguyen, 2008;Van den Berg and Nguyen, 2011;Nguyen, 2013). Credit and transfers can help households who are affected by natural disasters smooth their consumption (Sawada, 2006).…”
Section: Resilience To Disastersmentioning
confidence: 99%
“…If, indeed, it is, the government may shift their focus at least partly away from direct provision of credit to stimulating the linkages between the formal and the informal credit markets, especially given the mixed results of existing impact studies for (mostly) formal credit. Using the Vietnam Living Standard Surveys (VLSS) for 1993 and 1998, Quach and Mullineux () found that total credit helped increase household expenditure. Similarly, Nguyen () found that microcredit from Vietnam Bank for Social Policies had positive effects on income, consumption, and poverty reduction of borrowers in the rural areas using the VHLSS for 2002 and 2004.…”
Section: Introductionmentioning
confidence: 99%
“…These variables include access to credit ( Credit ) and household demographic characteristics (X), such as home ownership status and education level of the household members. As indicated by Quach et al. (2005), household credit has a positive effect on the economic welfare of poor households in rural Vietnam, since it may provide a source of funding for households to carry out entrepreneurial activities.…”
Section: Methodology and Datamentioning
confidence: 99%